Analysis of Islamic Law and Positive Laws for Fathers Who Do Not Support Their Children After Divorce - Jannah, Raudlatul; Quthny, Abu Yazid Adnan; Nugroho, Irzak Yuliyardy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Fulfillment of divorced children: Most fathers do not carry out their obligations to support their children and there are no sanctions for fathers who have carried out these obligations. This is the background to the issues raised, namely what are the legal sanctions for fathers who do not carry out their support obligations towards their children after divorce and what are the provisions on the father's support obligations towards children from the perspective of Islamic law and positive law in Indonesia. This type of research is library research, with primary legal materials and secondary legal materials and then analyzed as expected based on normative descriptive analysis. From the results of this research, it shows that the legal sanctions for fathers who do not support their children after divorce from an Islamic legal perspective have disparity, namely the opinion of Hanafi scholars that the child's previous support becomes the father's debt even though the father is poor, so that by the time the father is able to then father must replace it. However, if the father is capable but refuses or even does not provide support for the child, the judge is obliged to force the father to pay the support. According to the opinion of the Syafi'i Hambali and Maliki Schools, the child's past documents are invalid unless there is a decision from a judge, whereas according to positive law in Indonesia, legal sanctions for a father who neglects his obligations, namely supporting children after divorce, can be subject to civil and criminal law sanctions.